2021
DOI: 10.1186/s12891-021-04328-z
|View full text |Cite
|
Sign up to set email alerts
|

Value of passive anterior tibial subluxation on axial MRI in identifying anterior cruciate ligament functional deficiency in patients with advanced anteromedial osteoarthritis of the knee: a case-control study

Abstract: Background A functionally deficient anterior cruciate ligament (ACL) is considered one of the contraindications in unicompartmental knee arthroplasty (UKA). But there is still a lack of standardized and reproducible methods to assess ACL functional integrity in patients with advanced anteromedial osteoarthritis of the knee (AMOA). This study explores the value of passive anterior tibial subluxation (PATS) on axial MRI in evaluating ACL status in this population. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It was worth mentioning that the predictive model in our study had a higher accuracy (AUC = 0.949) than the predictive index (AUC = 0.897) of Tao et.al. [ 35 ], and higher sensitivity (96.2%) than the predictive index (55.0% and 93.3%) of Tao et.al. [ 35 ] and Johnson et.al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was worth mentioning that the predictive model in our study had a higher accuracy (AUC = 0.949) than the predictive index (AUC = 0.897) of Tao et.al. [ 35 ], and higher sensitivity (96.2%) than the predictive index (55.0% and 93.3%) of Tao et.al. [ 35 ] and Johnson et.al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the relationship between intraoperative findings of ACL and preoperative evaluations with physical examination, radiographs, or MRI [ 15 , 21 , 35 ]. Waldstein et.al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was no statistically significant difference in the diagnostic accuracy of a single parameter of radiography and MRI. A functionally-deficient ACL is currently considered to be contraindicated for UKA [ 18 ]. Therefore, whenever possible, preoperative MRI should be performed to help evaluate the ACL functional integrity and optimize subsequent operative plans.…”
Section: Discussionmentioning
confidence: 99%